2017
DOI: 10.1177/1010428317705034
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 5 promotes the migration and invasion of hepatocellular carcinoma via increasing the transcription of hypoxia-inducible factor-1α under hypoxia condition

Abstract: Hypoxia plays a critical role in the progression and metastasis of hepatocellular carcinoma by activating the key transcription factor, hypoxia-inducible factor-1. This study aims to identify the novel mechanisms underlying the dysregulation of hypoxia-inducible factor-1α in hepatocellular carcinoma. We found that histone deacetylase 5, a highly expressed histone deacetylase in hepatocellular carcinoma, strengthened the migration and invasion of hepatocellular carcinoma cells under hypoxia but not normoxia con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Acetylation is an important posttranslational modification of a protein. This modification is found widely in eukaryotic cells and occurs during the physiological activities at various stages (Kimura et al, 2005;Ishfaq et al, 2012;Lu et al, 2014), from regulating the function of proteins, especially in terms of protein stability (Zhou et al, 2016), to intracellular signal transduction (Batta et al, 2007;Tang et al, 2007;Spange et al, 2009), disease and other physiological processes (Batta et al, 2007;Iyer et al, 2012;Marouco et al, 2013;Ye et al, 2017). Acetylation occurs on the ε-amino group of lysine residues (Lu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Acetylation is an important posttranslational modification of a protein. This modification is found widely in eukaryotic cells and occurs during the physiological activities at various stages (Kimura et al, 2005;Ishfaq et al, 2012;Lu et al, 2014), from regulating the function of proteins, especially in terms of protein stability (Zhou et al, 2016), to intracellular signal transduction (Batta et al, 2007;Tang et al, 2007;Spange et al, 2009), disease and other physiological processes (Batta et al, 2007;Iyer et al, 2012;Marouco et al, 2013;Ye et al, 2017). Acetylation occurs on the ε-amino group of lysine residues (Lu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By bioinformatics analysis and microarray technology, functions of some differentially expressed genes (DEGs) in HCC have been explored, which paved the way for exploring complicated process in the occurrence and development of HCC [ 5 , 7 9 ]. As an important part of participating in life activities, transcription factors (TFs) have been reported to play an important role in the development of HCC by numerous studies [ 10 , 11 ]. A work by S. Hua et al found that ETS1, a cancer-related TF, could through interaction with miR-139-5p inhibit cell proliferation, migration, and invasion in HCC [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, poor clinical outcome, i.e., low overall and disease-free survival, was associated with overexpression of HDAC5 in pNET tissue [ 21 ]. Additionally, expression changes of HDAC5 were found, e.g., in hepatocellular carcinoma [ 22 , 23 ], lung cancer [ 24 ], and colon cancer [ 25 ], thus underlining its role in oncogenesis. Several studies, additionally, have shown a significant cytotoxic effect of various HDAC inhibitors (mostly pan-HDAC specificity) in pNET cell lines in vitro [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%